Mikhaïl Pletnev conducts Glazunov and Tchaikovsky - With Janine Jansen Verbier Festival 2017 - Glazunov, Aleksandr Konstantinovich 1865-1936; Tchaikovsky, Peter Ilich 1840-1893; Tchaikovsky, Peter Ilich 1840-1893 (Idéale Audience - medici.tv, 2017)
Mikhaïl Pletnev and the Verbier Festival Orchestra bring the 2017 Verbier Festival to a close with a concert dedicated to Russian composers. In this first part, they perform Glazounov's From the Middle Ages and Tchaikovsky's Souvenir d'un lieu cher. They are joined by Janine Jansen for Tchaikovsky's glorious Violin Concerto. The evening begins with a rare treat: the Prelude from Glazunov's 1902 orchestral suite From the Middle Ages. Evoking medieval Europe through orchestral music on an operatic scale, the suite portrays a passionate young couple, blissfully ignorant of the furious storm that surrounds them. The brilliant violinist Janine Jansen then takes the stage to perform Tchaikovsky's beloved Violin Concerto in D Major, one of the most beautiful and technically-challenging of the genre. Despite the concerto's success, Tchaikovsky never wrote another work of its kind
Keywords: Orchestre, Musique d'; Concertos (Violon); Concertos; Orchestral music; Concertos (Violin); Webcast; Concert films; Arrangements (Music); Internet videos; Arrangements (Musique); Concerts filmés; Vidéos sur Internet